Multi-band frequency selective metasurface based filter for WLAN and X-band EMI shielding applications - Haider Ali; Bilal Tariq Malik; Laeeq Riaz; Muhammad Farhan Shafique; Slawomir Koziel (Scientific Reports)
Abstract In this paper, a double-sided planar frequency selective metasurface (FSMS) has been presented for airborne electromagnetic interference (EMI) shielding applications. The proposed structure uniquely combines two narrow bands of WLAN (2.4 and 5.8 GHz) and the entire bandwidth of the X-band (8–12 GHz) spectrum. The proposed FSMS unit element (UE) is designed on a double-sided Rogers 5870 substrate with a total dimension of 11.4 × 11.4 mm2. The proposed UE design has a compact and symmetric layout. It is polarization-independent and has a stable angular response for up to 45o oblique angle of incidence. In addition, the low profile of the FSMS makes it appropriate for conformal surfaces. The proposed design has been backed by detailed explanations of the physical phenomena of current and field distribution and equivalent circuit models. For experimental validation, a 20 × 13 element FSMS with a total footprint of 229 × 152 mm2 is fabricated and experimentally validated. The simulated and measured characteristics and the equivalent circuit model predictions are well-aligned, which corroborates the high performance of the proposed design. The proposed FSMS features a novel and straightforward structure with multiband operation, stable incident angle output, polarization insensitivity, and scalability, making it a potentially attractive candidate for WLAN and X-band EMI shielding applications.